The The Relationship Between Lactation Period With Colostrum Age And Colostrum Fat Content Of FH (Friesian Holstein) At Kpsp Setia Kawan, Pasuruan - Anggriana, Livia Dwi; Surjowardojo, Puguh (Program Studi Peternakan Universitas Muhammadiyah Sidenreng Rappang, 2023)
Colostrum is the milk secreted by the mother cow on the first day until the fourth day of milking after giving birth sothat it becomes the main food for the calf. The decrease in the milk production of dairy cows is in line with the increasein the lactation period. The effect of lactation period and colostrum age on colostrum fat content needs to beinvestigated because many small farmers do not understand the importance of colostrum for calves, especiallycolostrum fat content. The research location is in the Cattle Farming Cooperative. Dairy (KPSP) Faithful Friend. Dairycows used were 23 FH cows with a sample of 115 samples with 3 lactation periods (1,2,3) and 1,2,3,4,5 milking days.The method used is the case study method and sampling with purposive sampling. The variables used were lactationperiod, age and colostrum fat. data were analyzed using simple linear regression and correlation then analyzed usingdescriptive results. The relationship between lactation period and colostrum fat content is Y 7.43 + 0.03X, which meansthat every increase of 1 lactation period will result in an increase in colostrum fat content of 0.03%. With a correlationcoefficient (r) of 0.013 and a determination coefficient (R2) of 0.01%. while the average age of colostrum with thehighest colostrum fat content on the first day was 8.79 while the smallest fat content on the fifth day was 5.85. Basedon the results of the study it can be concluded that lactation period is not associated with the highest colostrum fatcontent on day 1 and the lowest on day 5.Keywords: Colostrum, lactation period, colostrum age, fat